Teaching english to three to five year old children at Centro Sol de Talentos pre-school through songs and games - Cabrera Carchipulla, Verónica (2010)
Our research study is based on the study of songs and games as resources for the teaching and learning of English as a foreign language to young children. Our primordial contribution the cognitive development of kids is to help them communicate ideas through the environment where they live in; therefore, we want to use them to create a fun and interesting environment where preschool they may feel sure to participate in a class through songs and games while trying to develop some abilities and skills. Preschool-children do not connect logical things because they assimilate things with objects and according Piaget´s theory, cognitive development is connected to the four stages, which we focused the pre-operative stage says that children between two and six years old can associate words and things through symbols. That is why it is important the use of songs and games to improve the children s language learning and help them develop their skills. Finally, songs and games are used as a great methodology for learning English to help children develop listening and speaking by participating in songs and games in oral communication